Patient-Reported Outcome Measures for the Assessment of Stress in Neurological Patients: An Integrative Review - Sairanen, Ilkka (Elsevier, 2025)
Background
Patient stress is often overlooked in the care of patients with neurological problems. Nursing theorists have previously heralded stress assessment through conceptual clarification, while clinical nurses in the health care system hold an ideal position for implementation of assessment and coordination of support. Integrated with a hospital assessment and support scheme, recognition of stress as a target of systematic assessment can lead to improved clinical outcomes.
Objective
The aim of the study was to describe and compare patient-reported outcome measures suitable for assessment of the stress response as symptoms in neurological patients.
Design
This study is an integrative review and concept development of patient stress based on qualitative and quantitative analysis of available self-reporting instruments.
Methods
Instruments were retreived with a systematic search from PubMed, CINAHL, PsychINFO and Web of Science reference databases on August 2, 2021. Search terms associated with the concept of stress symptoms were used. Instrument inclusion was done with the guidance of authoritative symptom inventories, with partial confirmation by a second author to mitigate bias. In the analysis, the instruments included in the review were quantitatively described and compared. Insights from the instrument composition led to clarification of our concept of stress response to further refine the list of instruments suitable for self-assessment of the stress status. This study was not registered.
Results
Based on the inclusion criteria, 23 patient-reported outcome measures extending over a variety of stress concepts were included. The similarity of items among the instruments implied a symptom cluster delineated by 59 common symptom subclasses that were grouped together in a re-classification of instrument items. A comparative quantitative analysis prompted us to distinguish the concept of stress response from antecedent, consequent, and related concepts as a manifestation of mental, somatic, and behavioral domains. Ten instruments with items covering the three domains, each with unique qualities regarding number of items, measured spread, and letter count were described.
Conclusions
Within an organizational framework, effective allotment among types of support can be founded on the patient's stress status and the stressors. The stress status manifests itself as a set of measurable symptoms. Optimal instruments for use in systematic clinical assessment of neurological patients’ stress status should satisfy the suggested specification of the stress response with a minimal number of items and concise wording. Finding and including the relevant instruments for analysis were the main limitation of the study.